Expert consensus on palivizumab use for respiratory syncytial virus in developed countries. (February 2020) - Luna, Manuel Sánchez; Manzoni, Paolo; Paes, Bosco; Baraldi, Eugenio; Cossey, Veerle; Kugelman, Amir; Chawla, Rupesh; Dotta, Andrea; Rodríguez Fernández, Rosa; Resch, Bernhard; Carbonell-Estrany, Xavier
Abstract: Respiratory syncytial virus (RSV) infection is a leading cause of hospitalisation in early childhood and palivizumab is the only licensed intervention for prevention. Palivizumab guidelines should reflect the latest evidence, in addition to cost-effectiveness and healthcare budgetary considerations. RSV experts from Europe, Canada and Israel undertook a systematic review of the evidence over the last 5 years and developed recommendations regarding prophylaxis in industrialised countries. Almost 400 publications were reviewed. This group recommended palivizumab for: preterm infants (<29 and ≤31 weeks gestational age [wGA] and ≤9 and ≤6 months of age, respectively; high-risk 32–35 wGA), former preterm children ≤24 months with chronic lung disease/bronchopulmonary dysplasia, children ≤24 months with significant congenital heart disease; and other high-risk populations, such as children ≤24 months with Down syndrome, pulmonary/neuromuscular disorders, immunocompromised, and cystic fibrosis. Up to 5 monthly doses should be administered over the RSV season. It is our impression that the adoption of these guidelines would help reduce the burden of RSV.